SOCIAL AND LABOUR RELATIONS: MANAGING THE STRUCTURE IN IMPLEMENTING INNOVATIVE CHANGES - Belyaev, Victor; Kuznetsova, Olga; Pyatkova, Oksana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Implementing innovation programmes often encounters employee resistance to change.  The paperprovides evidence that the essential characteristics of the causes for such resistance lie in the contents and structure of the social and labour relations. They manifest themselves as opportunism at work. The authors believe that this problem can be solved by developing K. Lewin’s and E. Schein’s change management models. While implementing innovative programmes by using one of these models, atthe opening stage, by the procedure developed by the authors, it is suggested to do  research aimed at identifying the contents of the social and labour relations that have been formed within an organisation in order to reveal the quantitative measure of opportunistic behaviour of personnel in their structure and their further correcting towards decreasing the potential of employee resistance to change. For this purpose, the authors developed five scenarios and tools for gathering data through an employee survey in the environment where implementing innovative changes is expected. The findings are supposed to be presented in the form of M. Porter’s diagram, on the axes of which are indicated the types of social and labour relations; it perfectly reveals problem areas in the general structure of the social and labour relations. It is the managerial impact on them that allows a decrease in employee opportunistic potential.  The evaluation of the methodical approaches, which the authors made in health care institutions, has shown that implementing innovation changes encounters much less employee resistance. Using this conceptual model of change management oriented towards changes in the structure of the social and labour relations allows an increase in efficiency and effectiveness of implementing innovative changes in organizations.